MULTIDIMENSIONAL RISK AND RELIGIOSITY TOWARDS INDONESIAN MUSLIMS’ SHARIA INVESTMENT DECISION - Irna Puji Lestari; Wenang Ginanjar; Ari Warokka (Journal of Islamic Monetary Economics and Finance, 2021)
The decision-making process for Sharia investment needs to consider the individual’s risk tolerance since every type of investment is closely attached to the risk-return trade-off. This study examines whether multidimensional risk tolerance and religiosity influence Sharia investment decisions. The study used 300 potential Muslim investors in Indonesia as the primary data source through an online survey with a convenience sampling method and analysed the data using Partial Least Squares Structural Equation Modelling (PLS-SEM). The results show that three multidimensional risks (risk propensity, risk attitude and risk capacity) have a significant effect on the Sharia investment decision. The research also tested the moderating effect of religiosity levels by performing Multi-Group Analysis (MGA) and found significant differences between risk propensity and sharia investment decisions among moderate and devout religious individuals.